VTE prophylaxis in trauma - Kitvoraphat, Kornpong; Kanlerd, Amonpon (Journal of the Association of General Surgeons of Thailand under the Royal of Patronage of HM the King, 2025)
Venous thromboembolism (VTE) remains a significant clinical concern, with an estimated global incidence of 900,000 cases annually. In Thailand, the precise incidence is underreported, but studies from Level 1 trauma centers suggest a VTE rate of approximately 2.8% in trauma patients. VTE risk is strongly influenced by the Virchow triad, highlighting the importance of early detection and prevention in high-risk populations, such as those with spinal cord injuries, pelvic fractures, or lower extremity trauma. Current strategies for VTE prevention focus on mechanical methods and pharmacological prophylaxis, most commonly with low-molecular-weight heparin. Key considerations include the timing of initiation, dosage, duration of prophylaxis, and patient-specific factors such as age, renal function, history of bleeding or allergic reactions, and coexisting injuries that may affect hemodynamic stability. Risk stratification and individualized prophylactic approaches are crucial for balancing the benefits of VTE prevention with potential complications. Emerging technologies and protocols aim to optimize screening thresholds and enhance early detection in trauma settings.